Caracterización del incumplimiento del esquema de vacunación en niños menores de 2 años del Centro de Salud N° 2 del cantón Loja - Loarte Loarte, Emily Ivanova (2024)
Non-compliance with the vaccination schedule represents a problem for Public Health since it has had an impact on the decrease in coverage and an increase in outbreaks of diseases that were previously controlled and eliminated. For this reason, the present study was proposed with the objective of identifying the characteristics of non-compliance with the vaccination schedule in children under 2 years of age at health center No. 2 in Loja canton, it was a study with a quantitative approach, with a non-experimental design, descriptive in scope and crosssectional, with the participation of 30 tutors, to whom a questionnaire validated by experts was applied, using the Fleiss Kappa statistical coefficient. Among the main results it was possible to identify that: most of the tutors are between 25 and 32 years of age (66.66%), they are women (90.00%), residents of the urban area (100.00%); in relation to the infants, the age of 17 to 19 months preponderates (40.00%) and they are mainly women (56.67%). The vaccines with the greatest delay were varicella (21.81%) and the second dose of MMR (18.18%). Regarding the most frequent reasons for noncompliance, the sociocultural factor predominated with forgetting the vaccination date (31.25%), followed by the infant's illness (22.58%) and lack of biologicals (18.75%), reasons that also presented significant percentages. In conclusion, there is non-compliance with the immunization schedule, especially with vaccines that represent a risk of transmission, and the reasons for not being vaccinated range from a sociodemographic, cultural, cognitive, institutional and pediatric level